PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN MODEL PEMBELAJARAN COURSE REVIEW HORAY (CRH) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA MATA PELAJARAN AKUNTANSI DASAR - Nely Hartika (FKIP, Universitas Banten Jaya, 2021)
This study aims to determine the Course Review Horay (CRH) learning model in basic accounting subjects and to find out the development of the Course Review Horay (CRH) learning model can improve student achievement in basic accounting subjects. This study uses R&D (Research and Development) with reference to Sugiyono's theory which consists of six steps, namely potential and problems, data collection, product design, design validation, design revision, and product testing. The population in this study were all students of class X Accounting at SMK Negeri 3 Serang City. The results of this study indicate that the assessment given by the material/content expert by lecturers and teachers. The results of the teacher's expert assessment of the material aspects and the truth of the content get a score of 3,3 in the valid category. The results of the lecturer's expert assessment of the material aspects and the truth of the content got a score of 3,3 in the valid category. The results of product trials in students get a score of 3,2 in the valid category. As for student achievement in the learning process with an average pretest score of 53 and a postest score of 85, there was an increase of 32.